2011
DOI: 10.1002/smr.576
|View full text |Cite
|
Sign up to set email alerts
|

A rule‐based model for customized risk identification and evaluation of task assignment alternatives in distributed software development projects

Abstract: Distributed software development imposes new project risks that are very different from the ones in collocated development and are overlooked easily. At the same time, they depend to a large extent on project-specific characteristics. Therefore, new methods for identifying these risks in distributed projects have to be developed. This article presents a model for identifying these risks at the beginning of a project. The model systematically captures experiences from past projects in a set of logical rules des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…For example, “information sharing among the distributed sites” is considered as the most important success factor for RCM practices in GSD context. The activities involved in the change management process are more communication and collaboration oriented 78 ; although to address the RCM process effectively, the frequent sharing of information is important 79 . Holtkamp et al 80 argued that the efficient information sharing mechanism in GSD could positively impact the RCM process.…”
Section: Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, “information sharing among the distributed sites” is considered as the most important success factor for RCM practices in GSD context. The activities involved in the change management process are more communication and collaboration oriented 78 ; although to address the RCM process effectively, the frequent sharing of information is important 79 . Holtkamp et al 80 argued that the efficient information sharing mechanism in GSD could positively impact the RCM process.…”
Section: Study Findingsmentioning
confidence: 99%
“…Tracking and control RCM activities at distributed sites were reported as an essential factor for the successful implementation of RCM activities in GSD context. The management of demanded requirement changes across the geographical boundaries is critical 79 . Hanisch and Corbitt 93 indicated that it is significant to track the root cause of demanded changes for effective RCM.…”
Section: Study Findingsmentioning
confidence: 99%
“…Although contributing to the body of knowledge, case studies describe context-specific approaches and, therefore, transferring the outcomes to another context usually requires setting up a new case study. A process simulation as presented in this article helps improving decision-making processes by constructing a parameterized simulation model, which allows for modeling the intended process (or a set of alternatives), feeding the simulation with (empirical) data from past projects, calibrate the simulation, and eventually conclude a feasible solution; a procedure that was, so far, successfully applied to other fields, e.g., risk management in distributed projects as presented by Lamersdorf et al (2012).…”
Section: Related Workmentioning
confidence: 99%
“…However, the art and science of GSD is still evolving and thus, immature leading to the need of sound research outputs to support the discipline. Maybe the most relevant effort can be considered the work of Lamersdorf , although the works by Doma et al . , Fernandez and Basavaraju , da Silva , Almeida et al .…”
Section: Introductionmentioning
confidence: 99%